The Relation of Community Values and Norms to the Practice of Pilgrimage in Mount Kawi, Indonesia - Mahatva Yoga Adi Pradana; Muhammad Mansur; Fajar Dwi Noviantoro; Ari Anggito (UIN Sjech M. Djamil Djambek Bukittinggi, 2023)
This study aims to see the relationship between community behaviour in practising at the tomb of religious figures in Mount Kawi, Malang Regency, Indonesia. The behaviour of pilgrims in visiting has a variety of motivations and interests. Mount Kawi is a pilgrimage tourism site with an exciting background. There are tombs of Islamic religious figures and places of worship of ethnic Chinese. The relationship between the two has an interesting relationship to know. Researchers use a qualitative approach by selecting several informants and processing the data qualitatively. The results showed that the relationship between people's behaviour in performing pilgrims leads to values, norms, and group identity. People's encouragement to visit tombs is more on the mundane aspect. Therefore, individual symbols appear that strengthen as a form of spirituality respectively. This research also impacts improving the quality of pilgrimage tourism, which has a pattern of making the tomb of religious figures its symbol.